2017
DOI: 10.1186/s40834-016-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive utilization and associated factors among women of reproductive age group in Southern Nations Nationalities and Peoples’ Region, Ethiopia: cross-sectional survey, mixed-methods

Abstract: BackgroundThough contraceptive utilization has comprehensive benefit for women, it was one of underutilized public intervention in Ethiopia and in the study area. Thus, assessing status and factors affecting contraceptive utilization among women of reproductive age group was found key step for program improvement.MethodsCommunity based cross-sectional study was conducted from March to April, 2015 in Southern Nations and Nationalities Peoples’ Region, Ethiopia. A multistage stratified cluster sampling method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
62
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 15 publications
29
62
2
2
Order By: Relevance
“…In line with previous literature (19,21,24,25,28), our ndings also revealed that women were less likely to use modern contraceptives with increasing age when controlling for other factors. Modern contraceptive use among women 45-49 years of age was lower than adolescent women (women within 15-19 years of age).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous literature (19,21,24,25,28), our ndings also revealed that women were less likely to use modern contraceptives with increasing age when controlling for other factors. Modern contraceptive use among women 45-49 years of age was lower than adolescent women (women within 15-19 years of age).…”
Section: Discussionsupporting
confidence: 92%
“…Married women who have used pills, injectables, implants, intra-uterine devices (IUDs), condoms, sterilization, diaphragms, spermicides, and sponges were categorized and coded as modern contraceptive method users (18), whereas non-users and a very few (less than 1%) traditional users were coded as non-users. Explanatory variables were categorized based on prior evidence (8,(19)(20)(21)(22)(23)(24)(25)(26). These include women's age, women's educational level, and women's occupation, place of residence, regions, religion, and husband educational level.…”
Section: Variable Selectionmentioning
confidence: 99%
“…is is owing to implants' fewer requirements of providers and a lesser quantity of contraceptive supplies than a program relying on short-acting methods [5]. Furthermore, implants prevent unintended pregnancies, reduce the number of abortions, and lower the incidence of death and disability related to complications of pregnancy and childbirth [6]. Use of implants also frees a woman from using injectable contraceptives every three months and daily pills during the intended birth intervals because they are effective in preventing pregnancy from 3 to 5 years [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that 58.9% of rural Nigerian women and 69.5% of urban Nigerian women were injectables users. Second: (Endriyas et al, 2017) who had studied contraceptive utilization and associated factors among women of reproductive age group in Ethiopia. They also revealed that injectable contraceptive method was the most common method used by (69.10%) of the Ethiopian women.…”
Section: Utilization Of Contraceptive Methodsmentioning
confidence: 99%
“…• Low (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) • Moderate (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) • High (34-44) Fourthly, Perceived barriers: It included (11items) from 11-44 and it ranked as follow:…”
Section: Tools Of Data Collection: Two Tools Were Used For Data Collementioning
confidence: 99%